PW 2163 Knowledge of heat emergencies and management among healthcare professionals and community dwellers: a qualitative study. (November 2018) - Ahmed, Naveed; Naeem, Rubaba; Khan, Uzma Rahim; Khan, Nadeem Ullah; Razzak, Junaid
Abstract : Weather-related disasters during the last 20 years have resulted in over 6 06 000 deaths and over 4 billion people requiring emergency assistance. Pakistan is one of ten countries with the highest number of people affected by weather-related disasters. The study aimed at exploring the knowledge among community dwellers and healthcare professionals on heat emergencies and its management. Six in-depth interviews (IDIs) with physicians and nurses and three focused group discussions (FGDs) in the urban slum community were conducted in November 2017 in Karachi, Pakistan. The FGD comprised of three groups of relatively homogenous participants; males from local community, females from local community or the community health workers (CMWs) exclusively. IDIs were conducted from emergency physicians and nurses from four local hospitals. Interviews were audio-recorded and transcribed in the same language. Thematic approach was applied to analyze the data with coding as free nodes and formation of themes and sub-themes. The results of FGDs revealed that there is an adequate awareness of heat related emergencies among the community, especially among women in our population. Vulnerable population groups identified by the community include males who are working outside in the sun, elderly and school going children. Community indicated the need for training and awareness that focuses on translating knowledge into practice. Key barriers identified by the community include lack of awareness, financial resources, construction and design of the houses, public transport, lack of open public spaces, limited availability of drinking water and electricity, and lack of well-functioning healthcare facilities. Findings from IDIs of healthcare staff revealed that, there is no standard definition of heat stroke and in current scenario the cases are diagnosed on clinical judgment. Healthcare professionals identified the need for heat alarm system and disaster preparedness planning, trainings, availability of life-saving drugs, and strengthening of the primary healthcare system. Findings suggest that there is sufficient awareness of the health risks due to exposure to extreme heat. For both community and healthcare providers, limited resources hampered translating that knowledge into practice.